Voltammetric-based immunosensing of Newcastle disease virus on polyethylene glycol-containing self-assembled monolayer modified gold electrode - Abd Muain, Mohamad Farid; Amir Hamzah, Amir Syahir; Chia, Suet Lin; Yusoff, Khatijah; Lim, Hong Ngee; Shinya, Ikeno; Ahmad Tajudin, Asilah (Academic Press Inc., 2025)
A voltammetric immunosensor for the detection of Newcastle disease virus (NDV) has been developed by employing polyclonal antibody targeting NDV (anti-NDV) as a bioreceptor. Anti-NDV was immobilized on polyethylene glycol (PEG)-containing self-assembled monolayer (SAM) which was activated with N-(3-dimethylaminopropyl)-N′-ethylcarbodiimidehydrochloride (EDC) and N-hydroxy succinimide (NHS) coupling on screen-printed gold electrode (SPGE). The introduction of PEG-containing SAM on the SPGE allowed the bioreceptor to covalently bound to the electrode surface whilst still providing a hydrophilic layer on the electrode which is important to greatly reduce non-specific bindings. The bioreceptor functionalized electrode was then allowed to be incubated with NDV-spiked samples. The electrode surface modification with PEG-containing SAM, immobilization of anti-NDV as bioreceptor, up to the detection of NDV were characterized electrochemically through differential pulse voltammetry (DPV) analysis in [Fe(CN)6]3- as the redox probe. Decrement of anodic current peak (Ipa) of [Fe(CN)6]3- was seen as the concentration of NDV increased from 0.156 to 20 HA μL−1 with the limit of detection (LoD) of 1.50 HA μL−1 at 3σ m−1. The detection of NDV in HA μL−1 unit in this study would ease interlaboratory interpretation as it was the same unit used in hemagglutination (HA) assay of conventional NDV diagnosis. The specificity of anti-NDV used as bioreceptor towards NDV was confirmed through western blot analysis, whilst the selectivity of the bioreceptor-functionalized electrode has been tested with allantoic fluid as the negative control in which no apparent changes of anodic peak (Ipa) has been seen. This simple, fast, and less laborious electrochemical detection method could become an alternative to the conventional method for NDV detection.